Kajian Perbandingan Debit Andalan Sungai Cimanuk Metoda Water Balance dan Data Lapangan - Bakhtiar, Bakhtiar (MEDIA KOMUNIKASI TEKNIK SIPIL, 2008)
Provision of an adequate quantity of water has been a matter of concern since the beginning of civilization. Rivers is an important water resource for water supply. The availability of water to be supplied for many purpose of demand is measured in discharge. There are several methods can be used to calculate and analyze it. In this research and paper two methods was used and compared. There are FJ Mock method called water balance method, compared with actual discharges that measured at field. From the process in analyzing and comparing its appeared that there is two views in evaluate the difference between calculating result and measuring result. First is in absolute amount, and second is in percentage of amount of the difference toward actual amount from measuring in field. The data in this research is used as the case study was taken from Cimanuk River. The conclusion is there will be better to look the difference between the results from calculating method and measuring method, in the absolute amount of discharge. Keywords: Available discharge, calculating method, measuring method, percentage value difference, absolute amount difference ABSTRAK Persoalan kecukupan jumlah ketersediaan air telah menjadi perhatian sejak awal peradaban manusia. Sungai adalah sumber alam penting untuk suplai terhadap kebutuhan air. Ketersediaan air untuk memenuhi berbagai kebutuhan diukur dengan debit. Terdapat berbagai metoda untuk menghitung dan menganalisa debit. Dalam tulisan dan penelitian ini dua metoda digunakan dan dibandingkan. Yaitu metoda FJ Mock yang disebut metoda neraca kesimbangan air, lalu dibandingkan dengan metoda hasil pengukuran langsung dilapangan. Dalam proses analisis muncul dua sudut pandang dalam membandingkan hasil kedua metoda tersebut, yaitu pertama adalah selisih absolute dari debit dan kedua adalah prosentasi selisih debit. Data untuk penelitian ini diambil dari Sungai Cimanuk, sebagai tempat studi kasus. Kesimpulan yang didapat dari penelitian adalah bahwa akan lebih baik membandingkan hasil perhitungan analisa antara metoda hitung dan metoda pengukuran lapangan dalam besaran selisih debit.Kata kunci : Debit andalan, metoda kalkulasi, metoda pengukuran, selisih nilai persentasi, perbedaan nilai absolutPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/3694[How to cite: Bakhtiar (2008), Kajian Perbandingan Debit Andalan Sungai Cimanuk Metoda Water Balance dan Data Lapangan, Jurnal Media Komunikasi Teknik Sipil, Tahun 16, Nomor 2, pp. 200-207]